Enantioselective synthesis of tarchonanthuslactone using proline-catalyzed asymmetric alpha-aminooxylation - George, Shyla; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2007)
A practical enantio selective synthesis of tarchonanthuslactone 1, an important natural product with a polyol unit, is described. The sequence of synthetic reactions involves proline-catalyzed alpha-aminooxylation and iodine-induced electrophilic cyclization as the chiral inducing steps. (c) 2007 Elsevier Ltd. All rights reserved.